Marketing public relations strategy of coffee shop business during COVID-19 pandemic - Hendrayani, Yani; Alkautsar, Muhammad Sulthan; Manihuruk, Hermina (PRofesi Humas, 2022)
In recent years, public interest in coffee shops has become a trend in Indonesia. However, in the Covid-19 pandemic era, there have been many changes in shopping patterns from offline to online, forcing coffee shops to adapt to new normal conditions and prepare MPR strategies following the conditions during the Covid-19 pandemic. Sallo Coffee is a coffee shop located in Jakarta. Maintaining relationships with customers for the long term is part of the job of Public Relations (PR). In this study, the author wants to know Sallo Coffee’s Public Relations marketing strategy in maintaining customer loyalty during the pandemic. What is the challenge of implementing a PR marketing strategy during the pandemic to maintain customer loyalty? The paradigm used in this study is constructivism, in which researchers research public relations to reconstruct the existing reality. The approach used is a qualitative approach with descriptive research through interviews, observations, and documentation. The results of this study are that the current PR concept cannot be implemented with PR marketing strategies during the pandemic become limited under government regulations. Instagram social media is one of the media to promote Sallo Coffee products and provide product information to maintain relationships with customers or customer relations. The Internet is critical because the pandemic situation does not allow for as much physical contact as one would expect. With promotions on Instagram and social media, it can also be effective in maintaining customer loyalty during the pandemic.